NaV1.6 regulates excitability of mechanosensitive sensory neurons. (13th May 2019) - Israel, Mathilde R.; Tanaka, Brian S.; Castro, Joel; Thongyoo, Panumart; Robinson, Samuel D.; Zhao, Peng; Deuis, Jennifer R.; Craik, David J.; Durek, Thomas; Brierley, Stuart M.; Waxman, Stephen G; Dib‐Hajj, Sulayman D.; et al.
Abstract : Key points: Voltage‐gated sodium channels are critical for peripheral sensory neuron transduction and have been implicated in a number of painful and painless disorders. The β‐scorpion toxin, Cn2, is selective for NaV 1.6 in dorsal root ganglion neurons. NaV 1.6 plays an essential role in peripheral sensory neurons, specifically at the distal terminals of mechanosensing fibres innervating the skin and colon. NaV 1.6 activation also leads to enhanced response to mechanical stimulus in vivo . This works highlights the use of toxins in elucidating pain pathways moreover the importance of non‐peripherally restricted NaV isoforms in pain generation. Abstract: Peripheral sensory neurons express multiple voltage‐gated sodium channels (NaV ) critical for the initiation and propagation of action potentials and transmission of sensory input. Three pore‐forming sodium channel isoforms are primarily expressed in the peripheral nervous system (PNS): NaV 1.7, NaV 1.8 and NaV 1.9. These sodium channels have been implicated in painful and painless channelopathies and there has been intense interest in them as potential therapeutic targets in human pain. Emerging evidence suggests NaV 1.6 channels are an important isoform in pain sensing. This study aimed to assess, using pharmacological approaches, the function of NaV 1.6 channels in peripheral sensory neurons. The potent and NaV 1.6 selective β‐scorpion toxin Cn2 was used to assess the effect of NaV 1.6 channel activation in the PNS. The multidisciplinary approach included Ca 2+ imaging, whole‐cell patch‐clamp recordings, skin–nerve and gut–nerve preparations and in vivo behavioural assessment of pain. Cn2 facilitates NaV 1.6 early channel opening, and increased persistent and resurgent currents in large‐diameter dorsal root ganglion (DRG) neurons. This promotes enhanced excitatory drive and tonic action potential firing in these neurons. In addition, NaV 1.6 channel activation in the skin and gut leads to increased response to mechanical stimuli. Finally, intra‐plantar injection of Cn2 causes mechanical but not thermal allodynia. This study confirms selectivity of Cn2 on NaV 1.6 channels in sensory neurons. Activation of NaV 1.6 channels, in terminals of the skin and viscera, leads to profound changes in neuronal responses to mechanical stimuli. In conclusion, sensory neurons expressing NaV 1.6 are important for the transduction of mechanical information in sensory afferents innervating the skin and viscera. Key points: Voltage‐gated sodium channels are critical for peripheral sensory neuron transduction and have been implicated in a number of painful and painless disorders. The β‐scorpion toxin, Cn2, is selective for NaV 1.6 in dorsal root ganglion neurons. NaV 1.6 plays an essential role in peripheral sensory neurons, specifically at the distal terminals of mechanosensing fibres innervating the skin and colon. NaV 1.6 activation also leads to enhanced response to mechanical stimulus in vivo . This works highlights the use of toxins in elucidating pain pathways moreover the importance of non‐peripherally restricted NaV isoforms in pain generation.